Embedding Building Information Modeling (Bim) Competencies in Quantity Surveying Education - Kwong, Chin Wei (2019)
BIM is now trending in the construction industry. BIM tools is known to be able to assist throughout a project lifecycle from conception to commission and operation. Hence, the supply and demand of the BIM skilled workforce will be an issue in the near future. Higher Education Institutions (HEI) has to act as a vehicle to produce BIM-ready graduates with an attempt to close the gap of demand for graduates with BIM competencies. This study aims to identify the competencies required to embed BIM into the Quantity Surveying education by exploring the knowledge and skills required and recommend BIM competencies to be embedded in the Curriculum Learning Framework of QS undergraduate programme. The scope of this study only focuses on individual competences. From the literature review, three (3) major group of competences are identified: Contextual, Behavioural and Technical competence. 45 BIM competencies obtained from the Initial BIM Learning Outcomes Framework by the Building Academy Forum can be categorised into the three (3) major group of competence, and into 14 groups of BIM Capabilities. Survey questionnaires are distributed to local Quantity Surveyors of various business nature. Factor analysis results indicate that BIM education has to be taught in three (3) stages, namely: Conception Stage, Implementation Stage and Optimisation Stage. BIM competencies that are lack of, also known as the knowledge gap, is identified and sorted into type of competences and stages of education matrix. Further analysis is carried out to pair the competencies found in RICS Assessment of Professional Competence’s (APC) and Rules and Syllabuses of the Professional Examinations for Quantity Surveying by Institute of Surveyors Malaysia in view of embedding the BIM competencies into the QS undergraduate programme’s Curriculum Learning Framework.